Evaluating The Practice of Wakalah bi Al-Ujrah in Fund Transfers: Insights from a Rural Islamic Bank in Indonesia - Nabila, Qoriatun; Faizah, Maftuhatul (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
This study examines the implementation of Wakalah bi al-Ujrah contracts in fund transfer services at BPRS Bhakti Sumekar, an Islamic rural bank in Indonesia. As a Shariah compliant agency-based contract, Wakalah bi al-Ujrah allows customers to authorize the bank to conduct transactions on their behalf in exchange for a service fee. Using a qualitative case study approach, data were collected through interviews, observation, and document analysis. The findings show that while the contract structure aligns with Shariah principles, operational inefficiencies such as system disruptions and limited customer understanding affect service quality and consistency. This research highlights the need to strengthen internal procedures, improve customer education, and invest in operational infrastructure to enhance both efficiency and Shariah compliance in Islamic rural banking practices.